Introduction of Calopogonium mucunoides in hill country through grazing cattle - Simão Neto, Miguel; Cruz Filho, Agostinho Beato da (Pesquisa Agropecuaria Brasileira, 2014)
The persistance of calopo (Calopogonium mucunoides) seedlings emerged from dung patches spread out by cattle fed with this legume seed was studied in a preliminary trial carried out in five molasses grass (Mellinis minutiflora) pastures on a hill country of the Zona da Mata (Minas Gerais, Brazil), The legume seed were fed to five european-zebu cross heifers, mixed in a basal diet, during five consecutive days. Two weeks after the feeding of the seeds, 50 dung patches/pasture with seedlings of calopo were chosen and marked at random. Six months later, the persistance of the seedlings and the area covered by the legume plants were measured. About 76% of the dung patches had calopo plants which covered an average area of 966 cm2 /dung patch. Practical implications of these results for the dissemination of legume species through grazing animals are discussed.